‘Care-less whispers’ in the academy during COVID-19: A collaborative autoethnography - Paula Natalie Stone; Adele Phillips; Kerry Jordan-Daus (PRISM)
This collaborative autoethnography (Bochner and Ellis, 2016) has created a space for three women academics from working-class heritage, navigating the liminal and temporal space of the COVID-19 pandemic within a post-1992 Higher Education Institution, to explore the social relations of one Higher Education Institution and confront their lived experiences. The stories shared in this paper are analysed through a ‘care-less’ (Rogers, 2017) lens, which asks the academy to recognise and confront the duplicity and self-glorification of policy and practice, that might be viewed as acts of normalising and supporting care-less cultures and behaviours. The paper raises questions about social justice, diversity and inclusion, the intersectionality of class and gender, and the inequity of the lived experiences from those who sit on the margins. The paper is the first collaborative writing project from a newly formed staff network of academics who come from working-class backgrounds, and we are intentional in our commitment to support each other as new researchers, giving agency in support of the other to find their voice.